Human Sexual Dimorphism in 2D:4D Digit Ratio & Brain Sex: Hormones vs. Genes. - Saleh, Saad , M. (Iraqi Journal of Cancer and Medical Genetics, 2014)
I n human hands, the relative lengths of the second (2D, or index) finger and fourth (4D, or ring) finger differ between males and females. The ratio of 2D length to 4D length known as the 2D:4D ratio, & its value is < 1 for most men and ≥ 1 for most women. This sexually dimorphic character of the limb was linked to sex steroids &genes. Fetal brain on the other hand develops in the male direction (during the intrauterine period) through a direct action of testosterone on the developing nerve cells, or in the female direction through the absence of this hormone surge. The objective of this study is to search whether there is any relationship between brain sex as determined by standard scientific brain sex tests & the 2D:4D ratio by measuring the length of index & ring fingers in human hands. A sample of 150 individual (80 male &70 female) aged 20-25 years old was tested in this study. The results showed a high significant difference in 2D:4D ratio between male & female(X ²= 42.75, P< 0.001, 1df.), & the masculine brain sex score was more obvious in males with low 2D:4D digit ratio in comparison with females (X2 = 6.653, P< 0.05, 1df.).The mean brain score in males with longer 2D than4D (10.33 ±2.000) is set near the lower border of the feminine brain score (10.70 ±2.115) with a significant statistical difference (X2=8.972,P<0.05, 1df.).